APLIKASI PEMBUATAN LAPORAN KEUANGAN BERBASIS WEB - Dadi Rosadi; Ussi Lousiani (STMIK Mardira Indonesia, Bandung, 2015)
Trade Company is a company that is more emphasis on the process of buying and selling for not doing the processing of goods. CV INDOSAINS was the same as other trading companies, more emphasis on the process of buying and selling of goods, therefore, documentation of financial transactions was only limited to the purchase and sale of goods.Documentation of transactions currently running on INDOSAINS CV is less integrated because there is no single data connection with other data. So the reporting process takes a long time. In addition, documentation of transactions according to the rules of good accounting records which requires adequate knowledge.With the recommended application it is expected that the transaction documentation will well integrated between one data with other data, so that the administration does not have to be a recapitulation of data for report generation because it can directly print the desired report and generate financial reports more quickly and accurately. Along with this application needs experts are expected to be overcome because the application is made in such a way that can be a substitute for expert help. Keywords: financial statements, web-based, automated financial transactions